The influence of physical activity on reducing ADHD symptoms – a systematic review - Kotulska, Maria; Jędrzejewska, Barbara; Lichman, Martyna; Borycka, Aleksandra; Lubczyńska, Zuzanna; Potocka, Zofia; Przeradzki, Jakub; Laskus, Paulina; Rząd, Katarzyna; Szyca, Magda (Journal of Education, Health and Sport, 2023)
Introduction and objective Attention deficit hyperactivity disorder (ADHD) is a disease affecting children and adults. Quality of life of patients suffering from ADHD is often significantly reduced. The most common treatment includes medication and psychotherapy. Although the treatment is often efficient there is still a necessity of exploring other types of therapy due to the material reasons and side effects of the medications. The aim of the study was to asses the state of the knowledge about the influence of physical activity on the occurrence of symptoms in patients suffering from ADHD. State of knowledge The most common ADHD therapy is based on pharmacological agents. Mechanism of action of the drugs is often based on the inhibition of the reuptake of noradrenaline and dopamine. It leads to the enhancement in their transmission and causes the alleviation in ADHD symptoms. Many studies indicate that physical activity increases the level of catecholamines as well. The effects of physical activity on ADHD symptoms could be similar to those invoked by stimulants then. In comparison to drug therapy, physical activity is devoid of side effects and less expensive. Methods and materials We conducted a literature review in march 2023 using PubMed and Google Scholar databases. We used the terms “Physical activity in ADHD treatment”, “ ADHD in adults”, “ ADHD in children”, “ADHD symptoms”, “ADHD treatment”. Summary According to many studies physical activity seems to be efficient in reducing ADHD symptoms. The benefits are more reliable in children due to the bigger amount of conducted studies. Further clinical, randomized trials especially in a group of adults are needed to access the efficiency of physical activity as a ADHD treatment.